2009
DOI: 10.1111/j.1601-183x.2009.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental delay in the Cln3Δex7/8 mouse model for Batten disease

Abstract: Juvenile neuronal ceroid lipofuscinosis (JNCL), also known as Batten disease, is a fatal inherited neurodegenerative disorder. The major clinical features of this disease are vision loss, seizures and progressive cognitive and motor decline starting in childhood. Mutations in CLN3 are known to cause the disease, allowing the generation of mouse models that are powerful tools for JNCL research. In this study, we applied behavioural phenotyping protocols to test for early behavioural alterations in Cln3Dex7/8 kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 31 publications
1
27
3
Order By: Relevance
“…S1). It is noteworthy that our results are not in agreement with the findings reported by Osorio et al [27] in which 8-week-old homozygous Cln3 Δ ex7/8 mice on a C57BL/6J background were found to have reduced exploratory activity (reduced rearing frequency and vertical locomotion) and to spend less time in the center of the chamber in an open field assay.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…S1). It is noteworthy that our results are not in agreement with the findings reported by Osorio et al [27] in which 8-week-old homozygous Cln3 Δ ex7/8 mice on a C57BL/6J background were found to have reduced exploratory activity (reduced rearing frequency and vertical locomotion) and to spend less time in the center of the chamber in an open field assay.…”
Section: Resultscontrasting
confidence: 99%
“…Again in contrast to the Osorio et al study [27], in which 8-week homozygous Cln3 Δ ex7/8 mice on a C57BL/6J background were reported to perform more poorly than wild-type mice on an accelerating rotarod, we found no genotypic differences in accelerating rotarod performance in 10- to 11-week-old Cln3 Δ ex7/8 mice on the C57BL/6N background (Fig. S3).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Osorio et al (2009) recently reported an impaired motor performance of 8-week-old Cln3 Δex7/8 mice in a constant speed rotarod test. Using a more challenging, accelerating rotarod test (0-37 rpm in 120 s), we found that Cln3 Δex7/8 mice already have a motor coordination deficit at the age of 7 weeks (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This motor deficit, that can be detected as early as on postnatal day 14, has been characterized using an accelerating rotarod test (0–30 rpm in 240 s) (Kovacs and Pearce, 2008; Kovacs et al, 2006; Weimer et al, 2009). Osorio et al (2009) recently reported an impaired motor performance of 8-week-old Cln3 Δex7/8 -knock-in mice in a constant speed rotarod test. Applying a more challenging, accelerating rotarod test (0-37 rpm in 120 s), we were able to detect the motor coordination deficit in 7-week-old Cln3 Δex7/8 -knock-in mice (see Fig.…”
Section: Discussionmentioning
confidence: 99%